Comparative Study of Alkali and Acidic Cellulose Solvent Pretreatment of Corn Stover for Fermentable Sugar Production - Qianqian Wang; Wei Wei; Xia Li; Jianzhong Sun; Jing He; Mingxiong He (BioResources, 2015)
As an immerging lignocellulose pretreatment strategy, cellulose solvent-based pretreatment can break down inter- and intra-molecular hydrogen bonds and disrupt the rigid structure of cellulose. Two cellulose solvent pretreatments were examined and compared in this study: NaOH/urea and concentrated phosphoric acid. Pretreated corn stover substrates were characterized by optical microscopy, confocal laser scanning microscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and chemical analyses. It was found that both alkaline- and acid-based cellulose solvent pretreatments can disrupt cell wall structures and cause partial dissolution of the cell wall components. The results indicated that the alkaline-based cellulose solvent was more effective at removing lignin as compared with the phosphoric acid-based cellulose solvent. The initial enzymatic saccharification rate of corn stover pretreated by alkaline-based cellulose solvent was greatly enhanced; complete saccharification of the glucans was achieved within 24 h at an enzyme loading of 15 filter paper units (FPU)/g substrate. The enzymatic digestibility of corn stover pretreated by phosphoric acid was lower than that of the alkaline-based system; this was probably caused by the presence of a high concentration of lignin.